ANALYSIS OF THERMAL BARRIER COATED PISTONS IN THE COMSOL AND THE EFFECTS OF THEIR USE WITH WATER plus ETHANOL DOPED BIODIESEL - Ertuğrul, İshak; Ülkir, Osman; Özer, Salih; Özel, Serkan (Vinca Inst Nuclear Sci, 2022)
In this study, the thermal analysis of an aluminum piston coated with MgOZrO2 to create a thermal barrier with the COMSOL multiphysics program and the chang-es in exhaust gas temperature, fuel consumption, and engine torque values ob-tained as a result of engine test experiments were examined. For this purpose, the MgOZrO2 coated and uncoated piston engine was started with biodiesel and 5% water + 15% ethanol doped biodiesel fuel at engine speeds of 1000 rpm, 1500 rpm, 2000 rpm, and 2500 rpm. In the thermal analysis results obtained in the COMSOL, it was found that the temperature values increased in the upper regions of the coat-ed pistons. Likewise, in engine experiments, increased exhaust gas temperature and engine torque showed a tendency to decrease fuel consumption values. It has been observed that the data obtained in the analysis in the COMSOL program are in parallel with the results of the engine experiments.
Keywords: COMSOL Multiphysics; thermal barrier coating; engine test; biodiesel; Combustion Performance; Emission; Diesel; Engine; Injection; Gas